Helicobacter zhangjianzhongii sp. nov., isolated from dog feces - Wang, Hairui; Gu, Yixin; Zhou, Guilan; Chen, Xiaoli; Zhang, Xin; Shao, Zhujun; Zhang, Maojun (Frontiers in Genetics, 2023)
In 2019, two distinct bacterial isolates were independently isolated from the fecal samples of separate dogs in Beijing, China. These cells exhibit microaerobic, are Gramnegative, motile, and possess a characteristic spiral shape with bipolar single flagellum. They display positive results for the oxidase test while being negative for both catalase and urease. These organisms measure approximately 0.2-0.3 μm in width and 4.5-6 μm in length. The colonies are wet, flat, grey, circular, and smooth with sizes ranging from 1-2 mm in diameter after two days of growth. However, strains may exhibit variations in size and morphology following extended incubation. Phylogenetic analyses based on the 16S rRNA gene and core genome indicated that these two isolates belong to the genus Helicobacter and formed a robust clade that was remains distinctly separate from currently recognized species. These two isolates shared low dDDH relatedness and ANI values with their closest species H. canis CCUG 32756 T , with these values falling below the commonly cutoff values for strains of the same species. The genomic DNA G+C contents of strain XJK30-2 were 44.93 mol%. Comparing the phenotypic and phylogenetic features between these two isolates and their closely related species, XJK30-2 represents a novel species within the genus Helicobacter, for which the name Helicobacter zhangjianzhongii sp. nov. (Type strain XJK30-2 T =GDMCC 1.3695 T ) is proposed.